Investigation into factors related to human development for competitiveness in the Jamaican public secondary educational system - Kelly-Stair, Sharon (Consortium Graduate School of Social Sciences, 1993)
This essay explored the impact of the requirements for technological development and competitiveness on the secondary education system. It identified cognitive and affective skills such as literacy, numeracy, creativity, and critical thinking as vital for the development of the technological capability necessary for Jamaica to be competitive
Keywords: Competition